High Resolution Position Monitoring of Suspended MEMS towards Biological and Chemical Sensors. Issue 1659 (22nd January 2014) - Putrino, G.; Martyniuk, M.; Keating, A.; Dell, J.M.; Faraone, L.
ABSTRACT: We present an integrated readout technique for interrogating the suspension height of micro-electro-mechanical systems (MEMS) structures. This readout technique is envisaged to be useful in applications such as MEMS-based biological and chemical sensing, where it is necessary to obtain the accurate position of a MEMS beam. The approach is based on the suspended MEMS structure modulating light transmission in an underlying optical waveguide via Fabry-Perrot phenomena. The performance of the technique is predicted via finite difference time domain (FDTD) simulations the results of which are confirmed by experimental measurements.